2022
DOI: 10.3390/microorganisms10051052
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Acinetobacter baumannii: In Vitro and In Vivo Activity, Limitations, and Combination Therapies

Abstract: The survival, proliferation, and epidemic spread of Acinetobacter baumannii (A. baumannii) in hospital settings is associated with several characteristics, including resistance to many commercially available antibiotics as well as the expression of multiple virulence mechanisms. This severely limits therapeutic options, with increased mortality and morbidity rates recorded worldwide. The World Health Organisation, thus, recognises A. baumannii as one of the critical pathogens that need to be prioritised for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 114 publications
(170 reference statements)
0
5
0
Order By: Relevance
“…Evidences report revealed that biofilm-producing A.baumannii nosocomial isolates are so common. The survival, proliferation, and epidemic spread of the biofilm-producing A. baumannii in hospital settings, which results in resistance to many commercially available antibiotics and the expression of numerous virulence mechanisms, can be linked to the alarmingly increased prevalence of this organism [1,48]. This is because the biofilm encourages microbial adhesion and long-term survival on biotic and abiotic surfaces, which contributes to chronic and persistent infections, antimicrobial resistance, and strong survival in the hospital environment, particularly from immunocompromised patients in intensive care units [1,2].…”
Section: Plos Onementioning
confidence: 99%
“…Evidences report revealed that biofilm-producing A.baumannii nosocomial isolates are so common. The survival, proliferation, and epidemic spread of the biofilm-producing A. baumannii in hospital settings, which results in resistance to many commercially available antibiotics and the expression of numerous virulence mechanisms, can be linked to the alarmingly increased prevalence of this organism [1,48]. This is because the biofilm encourages microbial adhesion and long-term survival on biotic and abiotic surfaces, which contributes to chronic and persistent infections, antimicrobial resistance, and strong survival in the hospital environment, particularly from immunocompromised patients in intensive care units [1,2].…”
Section: Plos Onementioning
confidence: 99%
“…Owing to this, efforts are currently being made on research in alternative antimicrobials which complement antibiotic therapy and help combat the further development and spread of resistance in the future [ 96 ]. Accordingly, particular focus has been awarded to biological control strategies due to their low resistant frequencies, environmentally friendly, cost effective, and self-sustaining abilities [ 97 ]. The review further highlights the alternative control strategies including plant extracts and microbially synthesised secondary metabolites such as biosurfactants against antibiotic-resistant K. pneumoniae .…”
Section: Alternative Control Strategies For Antibiotic-resistant ...mentioning
confidence: 99%
“…Acinetobacter baumannii is a Gram-negative bacterium that, over the last four decades, has become one of the most frequently encountered and problematic human opportunistic pathogens, largely due to its antimicrobial resistance profile 1 . As a cause of hospital-acquired infections, A .…”
Section: Introductionmentioning
confidence: 99%